High School Mathematics Curriculum Development Integrated with Character Education Within Project Assessment as Spiral System Leveled - Munawaroh, Siti Badriatul; Sukestiyarno, Yohanes Leonardus; Masrukan, Masrukan (Unnes Journal of Mathematics Education, 2017)
The purpose of this research are: (1) description of characteristics and (2) validate thesenior hight school of mathematics syllabus integrated character education with the project assessment, (3) test the effectiveness of the learning material of function in class X. Testing procedure of syllabus and learning used research development of Borg & Gall (1987). The data were processed with descriptive analysis, statistical test t test and regression. The results obtained by the integration of the 10 characters on the senior hight school of mathematics syllabus show a valid syllabus by experts with an average score of 4 (both categories), the maximum score of 5. Test implementation on learning reach effective: (1) the percentage of learners achieve mastery learning by 89, 5%; (2) an increase of characters curiosity of learners of meeting 1 to 2, up to 3, up to 4 each score gain of 0.17; 0.30; 0.31; (3) the influence of the curiosity of students to the learning outcomes of 48.9%, (4) the average learning outcomes of students experimental class (77.2) is better than the control class (76.2). Thus, each character can bring a change in behavior according to the character programmed and observed in the learning process in focus. Coordination learning at every level stated in the syllabus.